Making knowledge work for us: evidence from Europe and North America on the links between "intangible" factors and growth, competitiveness and jobs - Carroll, Charles (Statistical and Social Inquiry Society of Ireland, 1996)
The title of the Report of the Science, Technology and Innovation Advisory Council (Stationery Office, 1995) is a useful starting point for this paper. It suggests that the issue is not so much about of the formation of intellectual capital. The crux of the matter for industrial and business policies is how do we make it work for us to effect economic and business growth. As the Council?s report says, knowledge is not transformed into wealth in an institutional vacuum. It happens within a system, a context with many components such as law, industrial policies, tax systems, a culture of enterprise and the economics of particular market domains. The Council also points out that Ireland?s third level institutions have not been wanting in ground breaking achievements in science and technology. The development of innovative enterprises is the crucial issue and raises large questions about the quality of corporate management, which, in turn, raises even larger questions about the quality of corporate governance and the types of investor relationships that might be appropriate to a more innovative Irish economy. This, in turn, raises questions about the type of chief executive and senior manager capabilities that we require for the future if we agree that technology is central to business policy and achieving the strategic intent of the Irish State.
Symposium on Science, Technology, and Innovation: the implications of the STIAC Report for Ireland's economic development
Read before the Society, 16 November 1995
Keywords: Competitiveness; Intangibles; Job market; 314.15